Value of histopathologic analysis of subcutis excisions by general practitioners - Verweij Wim; Buis Pieter AJ; van Diest Paul J (BMC Family Practice, 2007)
Abstract Background Only around 60% of skin lesions excised by GPs are referred to a pathologist. Clinical diagnoses of skin excisions by GPs may not be very accurate. Subcutis excisions are rarely done by GPs, and there is hence little information in the literature on the histopathological yield of subcutis excisions by GPs with regard to malignancies. The aim of this study was to evaluate the yield of histopathological investigation of a relatively large group of subcutis excisions by GPs, with special emphasis on discrepancies between clinical and histopathological diagnoses of malignancy. Methods We investigated a series of 90 subcutis excisions, which was derived from a database of consecutive GP submissions from the years 1999–2000 where in the same time period 4595 skin excisions were performed by the same group of GPs. This underlines the apparent reluctance of GPs to perform subcutis excisions. Results The final diagnosis was benign in 88 cases (97.8%) and malignant in 2 cases (2.2%). Seven cases had no clinical diagnosis, all of which were benign. Of the 83 clinically benign cases, 81 (97.6%) were indeed benign and 2 (2.4%) were malignant: one Merkel cell carcinoma and one dermatofibrosarcoma protuberans. The former was clinically thought to be a lipoma, and the latter a trichilemmal cyst. The dermatofibrosarcoma protuberans presented at the age of 27, and the Merkel cell carcinoma at the age of 60. Both were incompletely removed and required re-excision by a surgical oncologist. Conclusion Histopathological investigation of subcutis excisions by GPs yields unexpected and rare malignancies in about 2% of cases that may initially be excised inadequately. Based on these data, and because of the relatively rareness of these type of excisions, it could be argued that it may be worthwhile to have all subcutis excisions by GPs routinely investigated by histopathology.